2003
DOI: 10.1191/0269215503cr583oa
|View full text |Cite
|
Sign up to set email alerts
|

Lower abdominal pressure versus external bladder stimulation to aid bladder emptying in multiple sclerosis: a randomized controlled study

Abstract: Abdominal vibration is an effective method of reducing PVR in MS patients and appears more effective than abdominal pressure alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…This method can only be used in toilet-trained children [8], but collecting of urine samples in children is a time consuming and stressful process. Although a bladder stimulator had been shown to improve symptoms and decrease residual bladder volume in adults with multiple sclerosis in previous studies [9,18], Davies et al [10] found no effect on time to obtain a urine sample in precontinent children when a vibrating bladder stimulator was used. Moreover, the mean time to obtain a urine sample in these children was 1 h, meanwhile considerably long.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This method can only be used in toilet-trained children [8], but collecting of urine samples in children is a time consuming and stressful process. Although a bladder stimulator had been shown to improve symptoms and decrease residual bladder volume in adults with multiple sclerosis in previous studies [9,18], Davies et al [10] found no effect on time to obtain a urine sample in precontinent children when a vibrating bladder stimulator was used. Moreover, the mean time to obtain a urine sample in these children was 1 h, meanwhile considerably long.…”
Section: Discussionmentioning
confidence: 96%
“…It is not suitable for newborns as they do not have a sphincter control. Herreros et al hypothesized that the use of some stimulation techniques [18] that facilitate emptying of the bladder in situations of bladder dysfunction could facilitate the collection of midstream urine samples in newborns, and developed a new non-invasive technique based on bladder stimulation and lumbar paravertebral massage maneuvers [12]. They reported that the new technique was safe, quick, and successful in collecting midstream CCU in newborns [12].…”
Section: Introductionmentioning
confidence: 99%
“…There is level Ib evidence that supra pubic vibration (“buzzer”) can help initiate detrusor contractions and improve bladder emptying in those with incomplete bladder emptying and detrusor overactivity22 but its effect is limited.…”
Section: Management Of Impaired Voidingmentioning
confidence: 99%
“…There are some stimulation techniques that facilitate emptying of the bladder in situations of bladder dysfunction 3. We hypothesised that the use of such methods in newborns could facilitate the collection of a clean-catch urine sample.…”
Section: Introductionmentioning
confidence: 99%